Increased striatal dopamine (D2/D3) receptor availability and delusions in Alzheimer disease - Suzanne Reeves; Richard G. Brown; Robert Howard; Paul M. Grasby (2009)
Objective: Dysfunction within corticostriatal dopaminergic neurocircuitry has been implicated in neuropsychiatric symptoms associated with Alzheimer disease (AD). This study aimed to test the hypothesis that the symptom domains delusions and apathy would be associated with striatal dopamine (D2) receptor function in AD. Methods: In vivo dopamine (D2/D3) receptor availability was determined with [11C]raclopride (RAC) PET in 23 patients with mild and moderate probable AD. Behavioral symptoms were measured using the Neuropsychiatric Inventory and the Apathy Inventory. Imaging data were analyzed using a region-of-interest approach. The potential confounding effects of age, sex, and disease stage were explored using a linear mixed model. Correlational and independent samples comparisons were used to examine the relationship between behavioral and binding potential (BPND) measures. Results: Mean [11C]RAC BPND was higher in patients with delusions (n = 7; 5 men) than in patients without delusions (n = 16; 6 men) (p = 0.006). When women were excluded from the analysis, [11C]RAC BPND was higher in men with delusions than in men without delusions (p = 0.05). Apathy measures showed no association with [11C]RAC BPND. Conclusions: Striatal dopamine (D2/D3) receptor availability is increased in Alzheimer disease patients with delusions, to an extent comparable to that observed in drug-naive patients with schizophrenia. Whether this represents up-regulation of dopamine (D2) or possibly dopamine (D3) receptors and how this relates to responsivity of the striatal dopaminergic system merit further exploration. AD = Alzheimer disease; AI = Apathy Inventory; AST = associative striatum; BPND = binding potential; CAMCOG = Cambridge Cognitive Examination; DA = dopamine; LS = limbic striatum; MMSE = Mini-Mental State Examination; MRC = Medical Research Council; non-AC = non–attenuated corrected; NPI = Neuropsychiatric Inventory; RAC = raclopride; ROI = region of interest; SMST = sensorimotor striatum.